The Contribution of Parties in Developing Curriculum and Strategies for Teaching Islamic Religious Content in Schools in The Digital Age - Damopolii, Mujahid; Ainiyah, Nur (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
Gaining a deep understanding of the curriculum development process and which parties are involved in the development of the Islamic religious education curriculum at the school level in an era that is now utterly digital technology is the primary goal of this study. We searched for data and information to answer this study through examined the literature of book publications and scientific articles. This study used an indepth interpretation approach and document analysis and data coding to produce valid evidence to answer this question. From the results of the study and discussion, it can be concluded that the parties have fully contributed to the development of the curriculum for teaching Islamic religious education in the digital era; Among others, policy making at the central level is forwarded by the education office in the provinces and ends with implementation and financial inclusion at the school unit level as well as involving the leadership of the parent committee and the wider community. Another contribution that is more important is the involvement of technology experts who accompany curriculum development. Mendapatkan pemahaman yang mendalam tentang proses pengembangan kurikulum dan pihak-pihak mana saja yang terlibat dalam pengembangan kurikulum pendidikan agama Islam di tingkat sekolah di era yang serba digital saat ini menjadi tujuan utama penelitian ini. Kami mencari data dan informasi untuk menjawab penelitian ini melalui telaah literatur publikasi buku dan artikel ilmiah. Kajian ini menggunakan pendekatan interpretasi mendalam dan analisis dokumen dan koding data untuk menghasilkan bukti yang valid untuk menjawab pertanyaan tersebut. Dari hasil kajian dan pembahasan, dapat disimpulkan bahwa para pihak telah berkontribusi penuh dalam pengembangan kurikulum pengajaran pendidikan agama Islam di era digital; antara lain pengambilan kebijakan di tingkat pusat diteruskan oleh dinas pendidikan di provinsi dan diakhiri dengan pelaksanaan dan inklusi keuangan di tingkat satuan sekolah serta melibatkan pimpinan komite orang tua dan masyarakat luas. Kontribusi lain yang lebih penting adalah keterlibatan ahli teknologi yang mendampingi pengembangan kurikulum.